ANALISIS BUDAYA ORGANISASI MENGGUNAKAN HOFSTEDE DAN ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT (OCAI)(Studi Kasus pada Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Bengkulu) - Herfianti, Meiffa; Nengsih, Mimi Kurnia; Ari Pribowo, M. Galy Njoman (Creative Research Management Journal, 2023)
Organizational culture affects a person's role in carrying out his role. The success of organizational culture is marked by changes in individual behavior that can be emulated by other individuals. This study aims to determine the organizational culture created in the Faculty of Economics and Business, University of Muhammadiyah Bengkulu. The method used in analyzing organizational culture is Hofstede's method and OCAI (Organizational Culture Assessment Instrument) analysis. The results of the analysis using Hofstede's cultural dimensions state that the Faculty of Economics and Business, Muhammadiyah University of Bengkulu is in an organizational culture that has an even distribution of power, is collectivistic, masculinity has a strong influence within the institution, the institution focuses on things that have certainty value, the institution concentrate more on matters that have a long-term, future-oriented nature, and implement pragmatic values and institutions that control the fulfillment of needs and regulations with strict social norms. Meanwhile, based on the OCAI analysis, the current organizational culture and the expected organizational culture in the future is the Clan organizational culture. This means that there is a match between the desires of the leadership and employees because they are in the same organizational cultural orientation, namely a friendly workplace where people share with each other like a big family.